PERSONAL BRANDING AYU CORNELLIA DALAM MENINGKATKAN BRAND AWARENESS AGENCY CORNELLIA & CO - Amanda, Eza Tri; Sugiantoro, Hari Akbar (Universitas 17 Agustus 1945 Surabaya, 2024)
This study aims to explore how Ayu Cornellia's personal branding on Instagram can enhance brand awareness for her agency, Cornellia & Co. By applying Peter F. Montoya's eight laws of personal branding, this research analyzes key elements of personal branding, including specialization, leadership, personality, distinctiveness, visibility, unity, persistence, and goodwill. The research method used is descriptive qualitative, with data collection techniques involving observation and documentation of Ayu Cornellia's Instagram content. The results show that Ayu Cornellia's personal branding effectively increases her agency's brand awareness through consistency in image and messaging. The uniqueness and integrity displayed by Ayu Cornellia in her posts attract audience attention and build strong relationships with them. These findings provide practical insights for marketing communication practitioners to leverage personal branding as an effective strategy for building and enhancing brand awareness in the digital era. Keywords: Personal Branding, Instagram, Marketing Communcation, Brand Awareness.